HOW MULTISPECIES INTERCROP ADVANTAGE RESPONDS TO WATER STRESS: A YIELD-COMPONENT ECOLOGICAL FRAMEWORK AND ITS EXPERIMENTAL APPLICATION - GARCIA-BARRIOS, Luis; DECHNIK-VAZQUEZ, Yanus A. (Frontiers of Agricultural Science and Engineering, 2021)
● A framework for multicrop advantage under varying watering conditions is provided. ● This framework clarifies the relation between multicrop overyielding and land use efficiency. ● A novel experimental setup was used to evaluate these theoretical developments. ● Theory and experiment conveyed precise understanding of overyielding scenarios. Absolute yield and land use efficiency can be higher in multicrops. Though this phenomenon is common, it is not always the case. Also, these two benefits are frequently confused and do not necessarily occur together. Cropping choices become more complex when considering that multicrops are subject to strong spatial and temporal variation in average soil moisture, which will worsen with climate change. Intercropping in agroecosystems is expected to buffer this impact by favoring resistance to reduced humidity, but there are few empirical/experimental studies to validate this claim. It is not clear if relatively higher multicrop yield and land use efficiency will persist in the face of reduced soil moisture, and how the relation between these benefits might change. Here, we present a relatively simple framework for analyzing this situation. We propose a relative multicrop resistance (RMR) index that captures all possible scenarios of absolute and relative multicrop overyield under water stress. We dissect the ecological components of RMR to understand the relation between higher multicrop yield and land use efficiency and the ecological causes of different overyield scenarios. We demonstrate the use of this framework with data from a 128 microplot greenhouse experiment with small annual crops, arranged as seven-species multicrops and their corresponding monocrops, all under two contrasting watering regimes. We applied simple but robust statistical procedures to resulting data (based on bootstrap methods) to compare RMR, and its components, between different plants/plant parts. We also provide simple graphical tools to analyze the data.